1997
DOI: 10.1515/hfsg.1997.51.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characteristics of Waterlogged Archaeological Wood

Abstract: Waterlogged wood samples 300 to 100,000 years old of Picea abies, Pinus silvestris and Quercus sp. from northern Europe (Norway, Sweden) that had been preserved in a glacier, burial grounds, house settlements, harbour installations and sunken ships in the sea were examined for changes in physicochemical characteristics as compared to recent wood. The results showed that in waterlogged wood of all species the solubility in 1 % NaOH (8.39-22.85 %) was found to be higher than that of recent wood (3.84-5.57%). Ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 11 publications
2
25
0
4
Order By: Relevance
“…The diffractograms were used to calculate the crystallinity index, CrI % (Passialis 1997), and the crystallite length, L hkl (Jahan and Mun 2005):…”
Section: Methodsmentioning
confidence: 99%
“…The diffractograms were used to calculate the crystallinity index, CrI % (Passialis 1997), and the crystallite length, L hkl (Jahan and Mun 2005):…”
Section: Methodsmentioning
confidence: 99%
“…In relation to the crystallinity index, one factor that directly contributes to the decrease it undergoes is the increase of lignin. Passialis [29] showed that in wood submerged for thousands of years the lignin content increases up to 3.6 times in comparison with new wood. Although the wood in the present study was not submerged, natural ageing may have caused changes in the chemical composition by decreasing the fraction of carbohydrate composites in favour of the lignin content.…”
Section: H Emc a Emc D ---------------=mentioning
confidence: 99%
“…This affirmation is related to the degree of crystallinity, as the ability of wood to take up water by sorption decreases as the degree of crystallinity of the material increases [24]. Some studies have been done on the degree of crystallinity and its possible implications in the hygroscopic response [29,37].…”
Section: Introductionmentioning
confidence: 99%
“…The research shows a positive correlation between severities of degradation of ancient wood and the relative extraction content of 1%NaOH solution in ancient wood compared with healthy wood [5]. The content of holocellulose can relatively be more accurate in reflecting the rotten degree of waterlogged wood [6][7][8]. The white rot fungi, which can degrade lignin, belong to aerobic fungi.…”
Section: Chemical Components Of Waterlogged Woodmentioning
confidence: 99%